Farmers’ Food Security in Forest and Peatland Fires Prone Areas of South Kalimantan, Indonesia - Rozaki, Zuhud; Meirani Rejeki, Tristya; Rahayu, Lestari; Fairuz Ramli, Mona (Jurnal Sylva Lestari, 2023)
Forest and peatland fires in Indonesia affect the lives of farmers near the prone areas, and their food security is impacted. This research aimed to examine the level of food security and identify the factors influencing it in the forest and peatland fires of South Kalimantan. One hundred farmers, considered vulnerable to peatland fires, from two subdistricts, namely Gambut District and Sungai Tabuk District, were interviewed. The study employed the Household Food Insecurity Access Scale (HFIAS) method, consisting of nine food conditions questions and logistic regression analysis. This study shows that the majority of farmers experience mild food insecurity. Land status, family size, fire rate, and land size affected the farmers’ food security. Disaster mitigation education may help reduce the impact of forest and peatland fires on farmers’ food security. Additionally, support from various stakeholders will strengthen food security efforts. Keywords: farmers, fires, food security, forest, peatland